Anisotropy study of multiferroicity in the pyroxene NaFeGe2O6. (20th January 2015) - Ackermann, M; Andersen, L; Lorenz, T; Bohatý, L; Becker, P
Abstract: We present a study of the anisotropy of the dielectric, magnetic and magnetoelastic properties of the multiferroic clinopyroxene NaFeGe2 O6 . Pyroelectric currents, dielectric constants and magnetic susceptibilities as well as the thermal expansion and the magnetostriction were examined on large synthetic single crystals of NaFeGe2 O6 . The spontaneous electric polarization detected below in an antiferromagnetically ordered state ( ) is mainly lying within the ac plane with a small component along, indicating a triclinic symmetry of the multiferroic phase of NaFeGe2 O6 . The electric polarization can be strongly modified by applying magnetic fields along different directions. We derive detailed magnetic field versus temperature phase diagrams and identify three multiferroic low-temperature phases, which are separated by a non-ferroelectric, antiferromagnetically ordered state from the paramagnetic high-temperature phase.